Otimização da programação da produção em sistema de produção de embutidos (SPEmb) - Rocha, Rony Peterson da (2015)
Many embedded products industries work with a variety of products on their production lines. This variety causes difficulties in fulfilling the tasks sequencing on equipments, since these processes present a high complexity of running productive operations. A way to solve this problem is to seek scheduling optimization, by applying mathematical models. In this study the main challenge points out to the scheduling optimization in an embedded production system, taking to consideration the function of minimizing the makespan and maximizing the profit. Thus, there were implemented three mathematical formulations with the objective of minimizing the makespan and maximizing the profit function. In the first formulation it was considered the possibility of multiple stages and unique machines, on the second, it was considered the possibility of multiple stages and parallel machines, the third considered multiple stages and identical parallel machines with the setup depending on the sequence, and lastly, on the fourth formulation there were considered all the information present in the representation of states and tasks network (STN) for a scheduling case with a long term horizon. The results showed the possibility of applying these models in embedded industries in both, short and long term.